Isolated Invasive Endomyocardial Cystic Echinococcosis Presenting with Heart Failure - Suleyman Ercan; Vuslat Bosnak; Murat Yuce; Vedat Davutoglu; Fethi Yavuz (Case Reports in Medicine)
Cardiac cystic echinococcosis is a rarely encountered parasitic infestation caused by Echinococcus granulasus larvae. Cystic echinococcosis hydatid composes 0.5–2% of all human cystic echinococcosis cases. Isolated cardiac involvement is very rare. Cardiac cystic echinococcosis hydatid generally accompanies another organ involvement, however, it might be isolated as in the present case and although rare and it can cause heart failure. We present a case of isolated apical cardiac cystic echinococcosis hydatid which leads to heart failure.